Improved anticoagulant effect of fucosylated chondroitin sulfate orally administered as gastroresistant tablets - Fonseca, Roberto J.C.; Sucupira, Isabela D.; Oliveira, Stephan Nicollas M.C.G.; Santos, Gustavo R.C.; Mourão, Paulo A.S. (Thrombosis and Haemostasis, 2017)
Fucosylated chondroitin sulfate (FucCS) is a potent anticoagulant polysaccharide extracted from sea cucumber. Its anticoagulant activity is attributed to the presence of unique branches of sulfated fucose. Although this glycosaminoglycan exerts an antithrombotic effect following oral administration, high doses are necessary to achieve the maximum effect. The diminished activity of FucCS following oral administration is likely due to its degradation in the gastrointestinal tract and its limited ability to cross the intestinal cell membranes. The latter aspect is particularly difficult to overcome. However, gastroresistant tablet formulation may help limit the degradation of FucCS in the gastrointestinal tract. In the present work, we found that the oral administration of FucCS as gastroresistant tablets produces a more potent and prolonged anticoagulant effect compared with its administration as an aqueous solution, with no significant changes in the bleeding tendency or arterial blood pressure. Experiments using animal models of arterial thrombosis initiated by endothelial injury demonstrated that FucCS delivered as gastro-protective tablets produced a potent antithrombotic effect, whereas its aqueous solution was ineffective. However, there was no significant difference between the effects of FucCS delivered as gastroresistant tablets or as aqueous solution in a venous thrombosis model, likely due to the high dose of thromboplastin used. New oral anticoagulants tested in these experimental models for comparison showed significantly increased bleeding tendencies. Our study provides a framework for developing effective oral anticoagulants based on sulfated polysaccharides from marine organisms. The present results suggest that FucCS is a promising oral anticoagulant.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Glycosaminoglycans; oral anticoagulants; antithrombotic drugs; oral delivery anticoagulant; drug development